Boosting the Tertiary Students’ Participation in Research Class through Group Investigation Teaching Model - Suwartono, S (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2016)
This study aimed to improve the tertiary students’ participation in the research class. It was conducted in the framework of a Lesson Study. Data were collected through observation, questionnaire, and testing. The data were analysed using descriptive statistics. In the study, a colleague served as the classroom observer and assisted the data analysis. The writer, who was the lecturer of Research in Language Teaching course, acted as the model teacher. The research indicated that the Group Investigation teaching model successfully improved the students’ participation in the research class.